Impact of environmental factors on the efficiency of tax organizations - Tsakas, Marios; Katharaki, Maria (Serbian Journal of Management, 2014)
The study examines the performance of tax organizations in Greece, based on data obtained from a sample of 35 tax offices. Performance evaluation was conducted using DEA with bootstrap methods. In addition, Tobit regression analysis was employed to examine the environmental variables that impact on the efficiency performance of these tax offices. From the analysis, weaknesses, and management issues are derived from the tax offices inefficiency. The general conclusion is that a robust governance structure within the tax office operational framework is needed in order to improve organisational efficiency.